2014
DOI: 10.2203/dose-response.14-012.vijayalaxmi
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phones, Non-Ionizing Radiofrequency Fields and Brain Cancer: Is There an Adaptive Response?

Abstract: ᮀ There is widespread concern among the general public regarding the ever increasing use of mobile phones. The concern is mainly because the antenna which transmits nonionizing radiofrequency fields is held close to the head during use and thus might cause brain cancer. By far, the largest epidemiological study was conducted by the INTER-PHONE study group and the results were published in 2011. The author's conclusions were (i) no increased risk of meningioma and glioma in mobile phone users and (ii) there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Vijayalaxmi and Prihoda analysed the INTERPHONE data and found decreased risks in 24.3% of studies and increased risks in only 0.7% of studies for meningioma, and 22.1% vs. 6.6% for glioma28. Furthermore, they proposed that the observed consistent and replicated pattern of reduced risk would be very unlikely to have occurred just by chance and that RF-EMF-induced AR might account for this phenomenon28. However, their conclusion could not explain the increased risks of both tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Vijayalaxmi and Prihoda analysed the INTERPHONE data and found decreased risks in 24.3% of studies and increased risks in only 0.7% of studies for meningioma, and 22.1% vs. 6.6% for glioma28. Furthermore, they proposed that the observed consistent and replicated pattern of reduced risk would be very unlikely to have occurred just by chance and that RF-EMF-induced AR might account for this phenomenon28. However, their conclusion could not explain the increased risks of both tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of long-term heavy use of mobile phones still need further investigation. Data from parotid gland tumors were provided only from 3 countries, still with not significative results (92). Overall, the weak results provided by the studies on the effects of EMF on brain tumors do not allow to state that EMF are an established cause of cancer, and are therefore not addressed in the recommendations to reduce cancer risk (93).…”
Section: Electromagnetc Radiation Pollutionmentioning
confidence: 99%
“…A more recent prospective study also revealed significantly decreased risk for glioma in mobile phone users [ 26 ]. A potential hypothesis of RF-induced “adaptive response” has been proposed recently for the observed decreased incidence of brain cancer in mobile phone users [ 27 , 28 ]. The detailed IARC evaluations were published in monograph #102 [ 29 ].…”
Section: Evaluationsmentioning
confidence: 99%
“…This is the first time any expert group used the term “protective effect” for the observed risk estimates which were below unity between mobile phone use and cancer. Vijayalaxmi and Prihoda [ 27 ] and Vijayalaxmi et al . [ 28 ] have proposed a hypothesis of RF-induced “adaptive response” to describe such protective effect.…”
Section: Evaluationsmentioning
confidence: 99%